0 - Editorial - Oloyede, Olajide (African Sociological Review, 2022)
COVID-19 impacts on teaching and research in the academy. We say this borne out of the different teaching arrangements in the academy – virtual or hybrid of virtual and limited classroom teaching. Research, especially on-site field research of the quantitative or qualitative type requiring engagement with research subjects, remains, in most cases, suspended. Yet, knowledge dissemination in the form of book publishing and articles in journal, is essential and must continue. Publishers – books and journals – have their teeth cut out in this regard. And so are we at the African Sociological Review. We endeavour to play a role in this circumstance of activity-restricted COVID-19 pandemic by not only fulfilling our mission of disseminating knowledge by regular publication of the journal, but increasing the number of peer-reviewed articles in the journal. We start with this issue of the journal which, as regular readers of the journal will observe, contains more articles than our standard number per issue. The peer reviewed papers that we publish in this issue of Vol 24, are research from Côte ďIvoire, Gabon, Lesotho, Nigeria, South Africa with contributors from these countries, France and Italy. We appreciate and express our gratitude to all the reviewers.